Disabilities are also legitimately medically interesting constraints on legitimate interests - Lim, Chong-Ming (2020)
What is it for something to be a disability? Elizabeth Barnes, focusing on physical disabilities, argues that disability is a social category. It depends on the rules undergirding the judgements of the disability rights movement(s). Barnes’ account may strike many as implausible. I articulate the unease, in the form of three worries about Barnes’ account. It does not fully explain why the disability rights movement is constituted in such a way that it only picks out paradigmatic disability traits, nor why only the traits identified by the movement as constituting experiences of social and political constraint count as disability. It also leaves out the contribution of people other than disability activists, to the definition of disability. I develop Barnes’ account. On my account, a person is disabled if she is in some state which is constitutive of some constraint on her legitimate interests. This state must be the subject of legitimate medical interest, and be picked out by the disability rights movement(s) as among the traits they are seeking to promote progress and change for. My account addresses the worries about Barnes’ account. It is also able to include all disabilities, rather than only physical ones.